2016
DOI: 10.1095/biolreprod.116.140780
|View full text |Cite
|
Sign up to set email alerts
|

Cystic endometrial hyperplasia–pyometra syndrome in bitches: identification of hemodynamic, inflammatory, and cell proliferation changes<sup><xref ref-type="fn" rid="afn1">†</xref></sup>

Abstract: Cystic endometrial hyperplasia (CEH)-pyometra syndrome is one of the most common diseases of noncastrated female dogs. However, determination of etiological mechanisms and differential diagnosis of CEH-pyometra syndrome are undefined. The aim of this study is to compare immunohistochemically the expression of cyclooxygenase-2 (COX-2) inflammatory mediator, Ki-67 antigen proliferation marker, vascular endothelial growth factor (VEGF-A) angiogenesis mediator and its FLT-1 and KDR receptors, and correlate with Do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 33 publications
3
21
0
1
Order By: Relevance
“…Our data show that untreated PH dogs had the highest vascularization score throughout the experimental period, as well as the highest immunostaining score for VEGF-A in the prostate epithelium, similarly to previous data on men [49,50] and dogs [35,51,52]. Moreover, positive correlation between prostate volume and local blood flow was observed for untreated and finasteride-treated dogs, suggesting that increased prostatic size is followed by a concomitant increase in local vascularization in PH dogs [18,20,31].…”
Section: Plos Onesupporting
confidence: 90%
See 1 more Smart Citation
“…Our data show that untreated PH dogs had the highest vascularization score throughout the experimental period, as well as the highest immunostaining score for VEGF-A in the prostate epithelium, similarly to previous data on men [49,50] and dogs [35,51,52]. Moreover, positive correlation between prostate volume and local blood flow was observed for untreated and finasteride-treated dogs, suggesting that increased prostatic size is followed by a concomitant increase in local vascularization in PH dogs [18,20,31].…”
Section: Plos Onesupporting
confidence: 90%
“…All immunohistochemical reactions were accompanied by a negative control as previously described [31,32], consisted of prostate tissue from the Untreated Group lacking application of primary antibody. For the positive control, we used canine mammary gland tumor, previously attested by others [33][34][35] and also as a guarantee of the cross-reactivity of the primary antibody with canine tissue.…”
Section: Immunohistochemical Reaction For Vascular Endothelial Growthmentioning
confidence: 99%
“…It has been suggested that during early feline pregnancy matrix metalloproteinases increase, playing an important role in vascularization and implantation (Agaoglu et al, 2016). In the case of pyometra, vascular endothelial growth factor and prostaglandins are the molecular mediators that may be involved in the vascular changes (Hagman, 2017;Jursza-Piotrowska & Siemieniuch, 2016;Veiga et al, 2017). The dissimilar signal pathways activated in these processes might explain the uterine blood flow difference found between PYO and PRG groups.…”
Section: Discussionmentioning
confidence: 99%
“…In dogs, Doppler ultrasound has proved to be able to differentiate pyometra from other uterine conditions (Batista et al, 2016;Veiga et al, 2017). However, the use of Doppler ultrasound to assess feline pyometra has not been reported so far.…”
Section: Introductionmentioning
confidence: 99%
“…In bitches with pyometra, endometrial hyperplasia, with or without luminal content, the uterine artery blood flow velocity was higher than in normal ones (Batista et al, 2016). Uteri of bitches with cystic endometrial hyperplasia-pyometra syndrome showed inflammatory process characterized by COX-2 expression, resulting in not only inflammatory and proliferative, but also vascular disorders, demonstrated by increased blood flow and lower vascular resistance (Veiga et al, 2017). In 2018, Doppler was also used to evaluate pyometra in cats.…”
mentioning
confidence: 99%